2018
DOI: 10.2174/1745017901814010001
|View full text |Cite
|
Sign up to set email alerts
|

Active Aging and Elderly’s Quality of Life: Comparing the Impact on Literature of Projects Funded by the European Union and USA

Abstract: Background:The objective of this research is to verify whether European projects on Active Aging (AA) and Elderly Quality of Life (Qol) funded by the Seventh Framework Programme (FP7) produce an impact on literature similar to projects funded by the National Health Institute (NHI) of the United States on international literature using well-known bibliometric indicators. This effort may be useful in developing standardized and replicable procedures.Methods:Fifteen randomly selected projects on AA and Elderly Qo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Finally, a search in some of the major scientific databases was conducted: Web of Sciences (WoS), Scopus and PubMed. Only one paper found on Scopus could be related to this study, but it compares the projects funded by the European Union about active aging and elderly's quality of life with projects funded by USA [11].…”
Section: P O S Tmentioning
confidence: 99%
“…Finally, a search in some of the major scientific databases was conducted: Web of Sciences (WoS), Scopus and PubMed. Only one paper found on Scopus could be related to this study, but it compares the projects funded by the European Union about active aging and elderly's quality of life with projects funded by USA [11].…”
Section: P O S Tmentioning
confidence: 99%
“…Finally, we conducted a search in main scientific databases including: Web of Sciences (WoS), Scopus and PubMed. Only one paper found on Scopus could be related to this study but it compares the projects funded by the European Union about active aging and elderly's quality of life with projects funded by USA [11].…”
Section: Identify the Need Of Mappingmentioning
confidence: 99%
“…Table 2 shows the obtained results regarding this mapping question. It can be observed that the majority of end-user related stakeholders correspond to institutions dedicated to provide different services to older persons (11) and informal carers (6). Related to the health sector, solutions engaging Pharmaceuticals (4), patients suffering different diseases (4) and Doctors (3) are the most common.…”
Section: Mq3: What Types Of Institutions Are Involved In the Project?mentioning
confidence: 99%
“…A study recently evaluated the impact on scientific literature of a sample of projects funded by the 7th European Union’s Framework Program for Research and Innovation (FP7) on Active Ageing (AA) and elderly quality of life (QoL) in comparison to the same number of projects funded by the USA’s National Institute of Health (NHI) [1]. The results show that the European and American projects have a similar impact in terms of a number of published articles and number of citations by published papers per single project.…”
Section: Introductionmentioning
confidence: 99%